Following policy: networks, network ethnography and education policy mobilities - Ball, Stephen J. (Journal of education policy, 2016)
Based on the 'case' of educational reform in India, this paper explores the emergence of both new trans-national spaces of policy and new intra-national spaces of policy and how they are related together, and how policies move across and between these spaces and the relationships that enable and facilitate such movement. The paper is an attempt to think outside and beyond the framework of the nation state to make sense of what is going on inside the nation state. In particular, it takes seriously the need to rethink the frame within and scales at which the new policy actors, discourses, connections, agendas, resources, and solutions of governance are addressed - and the need to move beyond what Beck calls 'methodological nationalism' . In other words, the paper argues that thinking about the spaces of policy means extending the limits of our geographical imagination. To address this argument, it combines the presentation and discussion of data with some more general discussion of policy networks and mobilities.